A phosphodiesterase 4-controlled switch between memory extinction and strengthening in the hippocampus - Roesler, Rafael; Reolon, Gustavo K.; Maurmann, Natasha; Schwartsmann, Gilberto; Schröder, Nadja; Amaral, Olavo B.; Valvassori, Samira; Quevedo, João (Frontiers in Behavioral Neuroscience, 2014)
Established fear-related memories can undergo phenomena such as extinction or reconsolidation when recalled. Extinction probably involves the creation of a new, competing memory trace that decreases fear expression, whereas reconsolidation can mediate memory maintenance, updating, or strengthening. The factors determining whether retrieval will initiate extinction, reconsolidation, or neither of these two processes, include training intensity, duration of the retrieval session, and age of the memory. However, previous studies have not shown that the same behavioral protocol can be used to induce either extinction or reconsolidation and strengthening, depending on the pharmacological intervention used. Here we show that, within an experiment that leads to extinction in control rats, memory can be strengthened if rolipram, a selective inhibitor of phosphodiesterase type 4 (PDE4), is administered into the dorsal hippocampus immediately after retrieval. The memory-enhancing effect of rolipram lasted for at least one week, was blocked by the protein synthesis inhibitor anisomycin, and did not occur when drug administration was not paired with retrieval. These findings indicate that the behavioral outcome of memory retrieval can be pharmacologically switched from extinction to strengthening. The cAMP/protein kinase A (PKA) signaling pathway might be a crucial mechanism determining the fate of memories after recall.